2021
DOI: 10.3847/2041-8213/ac082e
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Gravitational Waves from Two Neutron Star–Black Hole Coalescences

Abstract: We report the observation of gravitational waves from two compact binary coalescences in LIGO's and Virgo's third observing run with properties consistent with neutron star-black hole (NSBH) binaries. The two events are named GW200105_162426 and GW200115_042309, abbreviated as GW200105 and GW200115; the first was observed by LIGO Livingston and Virgo and the second by all three LIGO-Virgo detectors. The source of GW200105 has component masses -+ 8.9 1.5 1.2 and 130 Gpc yr 69 112 3 1 under the assumption of a b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
334
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 649 publications
(387 citation statements)
references
References 241 publications
17
334
1
Order By: Relevance
“…Since two small black holes merging would likely not produce electromagnetic emission, we can help constrain the nature of the merger by searching for electromagnetic emission. Alexander et al (2021b) and Thakur et al (2020), among others, have searched near the merger event for a GRB afterglow counterpart of GW190814 in the radio and optical. Alexander et al (2021b) found a promising candidate (Candidate 1) for the radio counterpart of GW190814.…”
Section: Gw 190814mentioning
confidence: 99%
“…Since two small black holes merging would likely not produce electromagnetic emission, we can help constrain the nature of the merger by searching for electromagnetic emission. Alexander et al (2021b) and Thakur et al (2020), among others, have searched near the merger event for a GRB afterglow counterpart of GW190814 in the radio and optical. Alexander et al (2021b) found a promising candidate (Candidate 1) for the radio counterpart of GW190814.…”
Section: Gw 190814mentioning
confidence: 99%
“…During the second half of the third Observing Run of Advanced LIGO and Advanced Virgo (O3b), there was the observation of GW signals from two CBC inspiral which are consistent with NS-BH binaries: GW200105 and GW200115 [217]. These discoveries represent the first confident observations to date of NS-BH binaries via any observational means.…”
Section: Ns-bh Detectionsmentioning
confidence: 79%
“…The direct detection of gravitational wave (GW) confirms a major prediction of Einstein's General Relativity (GR) and initiates the era of gravitational wave physics [1][2][3][4][5][6][7][8][9]. Anyway, not only General Relativity (GR) which based on the symmetric metric with Levi-Civita connection could produce GW events, but also the Teleparallel Gravity with Weitaenböck connection [10-13] could produce observable GW events.…”
Section: Introductionmentioning
confidence: 92%